Virtual reality in sports coaching, skill acquisition and application to surfing: A review - Farley, O. R. L.; Spencer, K.; Baudinet, L. (Journal of Human Sport & Exercise, 2020)
The last decade, notably the past two years, have seen signi?cant advancements in virtual reality (VR) technology, especially within the development of 3D and 360° virtual environments. Smart Phone technology now allows for head mounted display of this environment which is much more user friendly and cost effective. Sport training can now take full advantage of the improved quality of operating systems and as a result, VR provides visual simulations and immersive, interactive environments. VR technology is becoming more popular with evident influence on collecting various physiological aspects, identifying and improving sensorimotor capabilities, replicating competition and environment situations where reaction time is critical, and developing skill acquisition. This paper, therefore, reviews the existing literature relating to VR and the use of the technology used within sport, skill acquisition and coaching. Specifically, the paper describes VR, examines the uses of VR in sports, the applicability of methodological approaches used along with findings, limitations and the implications for coaching and athlete practice. Additionally, this review reports on VR used within skill acquisition learning/teaching and identifies how the technology can apply to surfing skill development. This paper will promote new ways to hone specific, hard to obtain skills, encouraging novel thinking for coaches.